2020
DOI: 10.1007/s12149-020-01544-w
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT of off-target lymphoid organs in CD19-targeting chimeric antigen receptor T-cell therapy for relapsed or refractory diffuse large B-cell lymphoma

Abstract: Objective The interplay between systemic inflammation, activity of lymphoid organs and lymphoma activity in CD19-targeting chimeric antigen receptor (CAR)-T-cell immunotherapy, and its significance for response and toxicity, is not well defined. Methods Using serial 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT), metabolic parameters of lymphoma and lymphoid organs were analyzed in ten patients receiving Tisagenlecleucel (an autologous CD19 CAR-T cell product) for rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 15 publications
2
40
2
Order By: Relevance
“…Although other small studies found an association between TT-PET and CRS [20,23], we did not nd association between PET variables at TD or TT and toxicity, possibly because of high prevalence of CRS and small numbers of high-grade CRS and ICANS.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although other small studies found an association between TT-PET and CRS [20,23], we did not nd association between PET variables at TD or TT and toxicity, possibly because of high prevalence of CRS and small numbers of high-grade CRS and ICANS.…”
Section: Discussioncontrasting
confidence: 99%
“…Several previous studies focused on the role of PET-CT in the mentioned time points [19][20][21][22][23]. In a model built by Vercellino et al for prediction of early progression, total metabolic tumor volume (TMTV) was the only PET parameter assessed.…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective report on 10 patients with aggressive lymphoma, underlined the importance of early evaluation of therapeutic efficacy, with all patients with a partial or metabolic response at 3 months having shown metabolic response at 1 month, and only one patient with unfavorable outcome experiencing early metabolic response (34).…”
Section: Typical Patterns Of Response and Progression On [18f]-fdg Petmentioning
confidence: 99%
“…Considering the significance of early PET evaluation for outcome prediction, recently Derlin and colleagues found that, for achieving remission, an early metabolic response at PET was required [ 53 ]. In a pilot study including patients who performed 18F-FDG PET/CT scans before and 1 month after CAR-T-cell therapy, Shah et al demonstrated that all patients that did not reach a complete response subsequently relapsed [ 52 ].…”
Section: Evidence Based Medicine Of Early 18f-fdg Pet/ct During Immentioning
confidence: 99%
“…Immunological mechanisms may also contribute to toxicity, for example with the cytokine release syndrome (CRS), caused by cytokines produced by both activated CAR-T cells and other immune cells [ 68 , 69 ], and the immune effector cell-associated neurotoxicity syndrome (ICANS) [ 52 , 53 , 70 ]. In terms of adverse effects, Whang et al found that higher disease burden, measured by MTV and TLG, was associated with more severe CRS [ 51 , 71 , 72 ].…”
Section: Evidence Based Medicine Of Early 18f-fdg Pet/ct During Immentioning
confidence: 99%